Komunikasi Positif sebagai Upaya Perlindungan Anak dari Kekerasan melalui Kegiatan Parenting pada Masyarakat Tangerang Selatan - Chandrawaty Chandrawaty; Susianty Selaras Ndari; Yunisa Dwi Anggraini (Atfaluna: Journal of Islamic Early Childhood Education, 2019)
The purpose of the community partnership program "(PKM) Positive Communication as an effort of child protection from violence Through Community Parenting Activities at Cempaka Putih Kec. Ciputat Timur Tangsel "is to increase parenting knowledge to parents in self help change the skilled to follow up in case violence in upbringing, so that the occurrence of a change of paradigm of parents in parenting without violence. Activities (PKM) Positive Communication as an Effort of Child Protection From Violence through Parenting in Kec. Cempaka Putih Kec. Ciputat Timur Tangsel is done through the training process with participatory methods. The participatory methods used to invite participants to participate in the training by revealing his experiences, formulate concepts of parenting based on the experience of the learning process and during training, and formulate a program first aid for cases of violence against children in their environment. The participants consisted of 50 people comprising community leaders and residents around. Methods and training plan compiled by the team (PKM) Positive Communication as an effort of child protection from violence Through Community Parenting Activities at Cempaka Putih Kec. Ciputat. Third, consultations with staff of the Indonesian child protection Commissionto the contents of the material. Fourth, the implementation of training activities and plan follow-up activities. Fifth, the evaluation activities and make good devotion in the form of an article or module. The results of the parenting provided to improve the knowledge and understanding of parental Communication As Positive Efforts for child protection from violence Through Parenting Activities on communities of South Tangerang.